Mental Circulation Mechanisms and its Cognitive Responses in Contemporary Industrial Product Design. (Journal of the College of Basic Education, 2025)
This research is concerned with studying the mechanisms of mental circulation and its cognitive responses in the design of the contemporary industrial product. The problem of the research is the lack of a clear conception of the role that is played by these mechanisms and their cognitive responses in such design. The goal of the research is to reveal such mechanisms and discuss the cognitive responses that is involved. The theoretical framework consist of three sections. The first of which is titled (Mental Circulation) .The second one is titled (The Cognitive Response), while the third section is titled (Mental Circulation Mechanisms in the Design of Contemporary Industrial Products), The research produced the following key findings and conclusions , Mental circulation processes are achieved by the ability to think and picture when creating a modern industrial product , The methods of intellectual reflection in the design of the industrial product in strangeness, as well as the level of its attractiveness to the recipient, are altered by explaining the process of optimal usage, as it is a reaction to human and aesthetic demands